Quality-of-Life after Anterior Skull Base Surgery: A Systematic Review - Kirkman, Matthew A.; Borg, Anouk; Al-Mousa, Alaa; Haliasos, Nikolaos; Choi, David (Journal of Neurological Surgery Part B: Skull Base, 2014)
Background Improved treatment and survival of patients with skull base tumors has made the assessment of quality-of-life (QoL) in this population increasingly important. This article provides a comprehensive systematic review pertaining to QoL assessment in adults undergoing anterior skull base surgery.Methods We performed a literature search using the electronic databases of Ovid Medline and Embase. Additional articles were identified through a search using the phrase anterior skull base. Further articles were sought through hand-searching relevant journals and reference lists of identified articles.Results Our search strategy identified 29 articles for inclusion in our systematic review, with considerable variation between studies in population characteristics, methodological design and quality, follow-up length, and outcome assessment. The most commonly used QoL tools were the Karnofsky Performance Status and the Anterior Skull Base Questionnaire. QoL following anterior skull base surgery appears to improve beyond preoperative levels in the months after surgery. For patients undergoing endoscopic skull base surgery, the gain in QoL appears to be greater and may manifest earlier, with no clear long-term deleterious effect on sinonasal outcomes compared with open surgery.Conclusions QoL after anterior skull base surgery in adults appears to improve within several months of surgery, but earlier and to a larger extent if the endoscopic approach is used. Given the relative paucity and heterogeneity of anterior skull base tumors, large-scale prospective multicentre studies utilizing valid and reliable multidimensional QoL tools are required. This may result in improved patient care, by understanding patients' needs better and facilitating the provision of reliable outcome data for clinical trials.
Keywords: anterior skull base surgery; endoscopic; functional outcomes; quality-of-life; tumor